Peran Hukum Kepailitan Dan Penundaan Kewajiban Pembayaran Utang (PKPU) Dalam Penyelesaian Sengketa Utang Piutang Di Indonesia - Dirgantara, Febrian; Putra, Arif Rachman; Darmawan, Didit; Khayru, Rafadi Khan; Wibowo, Agung Satryo (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
This study aims to provide a normative‑juridical analysis of the legal framework governing bankruptcy and The Suspension of Debt Payment Obligations (PKPU) under Indonesia’s Law No. 37 of 2004. Using a normative approach, the research examines the statutory foundations, core principles, and the mechanisms by which bankruptcy and PKPU procedures are implemented in resolving creditor‑debtor relationships in Indonesia. It addresses the eligibility criteria, procedural stages, and institutional roles involved both in initiating bankruptcy proceedings and in conducting the PKPU mechanism as a means to rescue the debtor’s business. The analysis finds that while Law No. 37 of 2004 offers robust legal instruments, its practical implementation still faces challenges such as limited transparency, potential moral hazard, and the need to bolster the role of administrators and judicial oversight. In particular, PKPU provides a valuable opportunity for debtors and creditors to negotiate debt restructuring before moving to liquidation, aligning more closely with principles of procedural justice and economic efficiency. Ensuring consistent enforcement and the integrity of legal actors is critical for the Law’s objectives to be fully realized in practice.